2021
DOI: 10.3389/fimmu.2020.599736
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Integrating the Complexity of Systemic and Pulmonary Immunopathology to Identify Biomarkers for Different Outcomes

Abstract: In the last few months, the coronavirus disease 2019 (COVID-19) pandemic has affected millions of people worldwide and has provoked an exceptional effort from the scientific community to understand the disease. Clinical evidence suggests that severe COVID-19 is associated with both dysregulation of damage tolerance caused by pulmonary immunopathology and high viral load. In this review article, we describe and discuss clinical studies that show advances in the understanding of mild and severe illness and we hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 193 publications
(245 reference statements)
0
14
0
1
Order By: Relevance
“…As expected, the reuse of transcriptome data from SARS-CoV-2-infected NHBE cells, a normal human bronchial epithelial cell line, evidenced enriched biological pathways associated with non-hemostatic inflammation, including upregulation of the IL-6 gene expression. A recent review paper from our team has reported the relationship between serum IL-6 levels and different outcomes of Covid-19 patients 90 : compared with severe patients, critical and mild patients have higher and lower IL-6 levels, respectively; and non-survivors exhibit significantly higher IL-6 levels than survivors with Covid-19. In vitro assays using Calu-3, A549, and NHBE cells have confirmed that SARS-CoV-2 infection induces IL-6 production 30 .…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the reuse of transcriptome data from SARS-CoV-2-infected NHBE cells, a normal human bronchial epithelial cell line, evidenced enriched biological pathways associated with non-hemostatic inflammation, including upregulation of the IL-6 gene expression. A recent review paper from our team has reported the relationship between serum IL-6 levels and different outcomes of Covid-19 patients 90 : compared with severe patients, critical and mild patients have higher and lower IL-6 levels, respectively; and non-survivors exhibit significantly higher IL-6 levels than survivors with Covid-19. In vitro assays using Calu-3, A549, and NHBE cells have confirmed that SARS-CoV-2 infection induces IL-6 production 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The latter should be considered in particular with respect to the recently described immunological profiles of COVID-19 lungs ( 63 ) suggesting a complex interplay of innate and adaptive immunity underlying the clinical picture. It has to be emphasized, however, that other anti-inflammatory treatment options, for example blocking interleukin-6 or inhibiting the C3 and C5 activation also showed a promising preclinical effect ( 64 ).…”
Section: What Does It Mean?mentioning
confidence: 99%
“…Allerdings zeigt die Auswertung vieler international durchgeführter Studien ein deutliches Biomarkerprofil in den Inflammationswerten während einer COVID-19-Pneumonie als Ausdruck des Zytokinsturms. Es scheint bei der Interpretation auf die Gesamtheit der Laborparameter anzukommen, nicht auf einen singulären Wert [ 25 ]. Tab.…”
Section: Exkurs Cryptococcus Neoformansunclassified